Characteristics of the Aragonitic Layer in Adult Oyster Shells, Crassostrea gigas: Structural Study of Myostracum including the Adductor Muscle Scar - Lee, Seung-Woo (Hindawi Publishing Corporation, 2011)
Myostracum, which is connected from the umbo to the edge of a scar, is not a single layer composed of prismatic layers, but a hierarchically complex multilayered shape composed of minerals and an organic matrix. Through the analysis of the secondary structure, the results revealed that a β-antiparallel structure was predominant in the mineral phase interface between the myostracum (aragonite) and bottom folia (calcite). After the complete decalcification and deproteinization, the membrane obtained from the interface between the myostracum buried in upper folia, and the bottom folia was identified as chitin. The transitional zone in the interface between the adductor muscle scar and folia are verified. The myostracum disappeared at the edge of the scar of the posterior side. From this study, the entire structure of the myostracum from the adult oyster shell of Crassostrea gigas could be proposed.